Personal bankruptcy law, wealth and entrepreneurship: Theory and evidence from the introduction of a "fresh start" - Frank M. Fossen (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
A personal bankruptcy law that allows for a fresh start after bankruptcy reduces the individual risk involved in entrepreneurial activity. On the other hand, as risk shifts to creditors who recover less of their credit after a debtor's bankruptcy, lenders may charge higher interest rates or ration credit supply, which can hamper entrepreneurship. Both aspects of a more forgiving personal bankruptcy law are less relevant for wealthy potential entrepreneurs who still risk losing their wealth, but tend not to face higher interest rates because they provide collateral. This paper illustrates these effects in a model and tests the hypotheses derived by exploiting the introduction of a fresh start policy in Germany in 1999 as a natural experiment, based on representative household panel data. The results indicate that the insurance effect of a more forgiving personal bankruptcy law exceeds the interest effect and on balance encourages less wealthy individuals to enter into entrepreneurship.
Keywords: K35; G33; L26; 330; personal bankruptcy law; insolvency; entrepreneurship; fresh start